Knowledge, Attitude and Practices of Barbers about Hepatitis B and C and its Transmission in Larkana City, Pakistan (Medical Forum Monthly, 2024)
Background: Blood borne diseases impose heavy burdens on national economies and individual families due to costs arising from acute and chronic morbidity and mortality. Globally, 2 billion people are infected with hepatitis B virus (HBV). An estimated 170 million persons are chronically infected with hepatitis C virus (HCV) and 3–4 million persons are newly infected each year.Transmission of hepatitis B & C through infected needles, blades, etc. is well known. Barbers are the important parts of community, as almost every man needs at least monthly visit to barber for hair dressing or shaving. In Pakistan the prevalence of shaving by barbers is reported to be as high as 34%–49% of the male population and it is important to know how barbers perceive the risks in relation to prevention of transmission of hepatitis B &CObjective: To assess the knowledge and attitude of barbers regarding HBV and HCV and find out practices among barbers which may be responsible for transmission of HBV and HCV.Study Design: Cross-Sectional StudyPlace and Duration of Study: This study was carried out in the Larkana city during the months of March 2010 to April 2012.Material and methods: A list of the barbers was obtained from the union of barbers and sample was drawn from that sampling frame. There were 422 barbers shops in the city. For sampling purpose Larkana city was arbitrarily divided into five zones (East, West, Central, South & North) and then 10 shops randomly selected from each zone. There were 156 barbers available and eligible for interview. After informed verbal consent, 132 barbers agreed to participate in the study. Data was entered, analyzed by Statistical Program for Social Sciences (SPSS) version 13.Results: A total 132 barbers were interviewed. The mean age of respondents was 28+ 10 years, mean years of experience in barbering was 12.7 +10. More than half (63.6%) respondents were married. Majority of the respondents (84.8%) were resident of urban areas. 64% barbers have had knowledge that hepatitis B & C can be transmitted through blood transfusion and sexual contact. Only 6.1% had been vaccinated against the hepatitis B. 70% of the barbers disposed of used blades in regular garbage. 82% washed hands before and after shaving each client, 92.4% cleaned their instruments with disinfectant after shaving the, 99.2% barbers change the blade for each clientConclusion: The knowledge of barbers regarding the transmission of hepatitis B & C was fairly good but majority of the barbers were not vaccinated against Hepatitis B though they were knew that vaccine is available against the hepatitis B